Assessing the Quality of Microvascular Breast Reconstruction Performed in the Urban Safety-Net Setting: A Doubly Robust Regression Analysis. Issue 2 (February 2019) - Offodile, Anaeze C.; Boukovalas, Stefanos; Muldoon, Lawrence; Lee, Clara N.
Abstract : Background: Safety-net hospitals serve vulnerable populations; however, care delivery may be of lower quality. Microvascular immediate breast reconstruction, relative to other breast reconstruction subtypes, is sensitive to the performance of safety-net hospitals and an important quality marker. The authors' aim was to assess the quality of care associated with safety-net hospital setting. Methods: The 2012 to 2014 National Inpatient Sample was used to identify patients who underwent microvascular immediate breast reconstruction after mastectomy. Primary outcomes of interest were rates of medical complications, surgical inpatient complications, and prolonged length of stay. A doubly-robust approach (i.e., propensity score and multivariate regression) was used to analyze the impact of patient and hospital-level characteristics on outcomes. Results: A total of 858 patients constituted our analytic cohort following propensity matching. There were no significant differences in the odds of surgical and medical inpatient complications among safety-net hospital patients relative to their matched counterparts. Black (OR, 2.95; p < 0.001) and uninsured patients (OR, 2.623; p = 0.032) had higher odds of surgical inpatient complications. Safety-net hospitals (OR, 1.745; p = 0.005), large bedsize hospitals (OR, 2.170; p = 0.023), and Medicaid patients (OR, 1.973; p = 0.008) had higher odds of prolonged length of stay. Conclusions: Safety-net hospitals had comparable odds of adverse clinical outcomes but higher odds of prolonged length of stay, relative to non–safety-net hospitals. Institution-level deficiencies in staffing and clinical processes of care might underpin the latter. Ongoing financial support of these institutions will ensure delivery of needed breast cancer care to economically disadvantaged patients. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III. Abstract : Evidence-Based Outcomes Article.